2016
DOI: 10.1590/1983-80422016243146
|View full text |Cite
|
Sign up to set email alerts
|

O processo de consentimento livre e esclarecido nas pesquisas em doença falciforme

Abstract: Sickle cell disease is a term that refers to a group of hemoglobinopathies associated with the presence of hemoglobin S. Occurring primarily in black population, and affecting mainly the most vulnerable, the homozygous form of the disease, sickle cell anemia, is considered an important public health problem in Brazil. Understanding scientific research as essential to promote health and improve the quality of life of people with sickle cell disease, the informed consent process should be done to overcome, as fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
2
0
6
Order By: Relevance
“…Foram identificadas seis normativas da CONEP 4,9-13 e 233 estudos, sendo 11 selecionados para avaliação e maior detalhamento quanto aos critérios estabelecidos para ética em pesquisas em ambiente virtual (online) [14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Foram identificadas seis normativas da CONEP 4,9-13 e 233 estudos, sendo 11 selecionados para avaliação e maior detalhamento quanto aos critérios estabelecidos para ética em pesquisas em ambiente virtual (online) [14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Resultsunclassified
“…A maioria dos trabalhos selecionados 14,17,[20][21][22][23][24] discutiu a Resolução CNS 466 4 , que trata da ética em pesquisa com seres humanos. Esta é vista como uma resolução longa e filosófica, em consideração aos referenciais bioéticos, quais sejam: respeito à dignidade, liberdade, autonomia, beneficência, não-maleficência, justiça e equidade aos participantes de pesquisa 22 .…”
Section: Discussionunclassified
“…Intense pain, successive infections, blood transfusions, frequent hospitalizations and the need for successive treatment exemplify the materialization of these adverse conditions. There is also social vulnerability, in which the injuries caused to the physical body can reflect on the individual's mental health and, consequently, on their social relationships [53]. In a study aimed at assessing the knowledge and practices of families involved in sickle cell disease in a city in Congo, it was found that more than half of parents do not feel guilty about their child's disease.…”
Section: Sickle Cell Anemia In the Biocultural Approachmentioning
confidence: 99%
“…The lack of knowledge about the disease causes embarrassment due to its appearances, such as yellowish eyes, short stature and fragile appearance. Problems arising from difficulties related to the provision of financial support and sex life, cause depression in these patients [53]. Therefore, Canesqui's considerations can be reiterated "[...] to approach the socio-cultural dimension of long-term illnesses means looking at the subject living with a condition that accompanies him everywhere [...]" [31].…”
Section: Sickle Cell Anemia In the Biocultural Approachmentioning
confidence: 99%
“…Dentre estas, o destaque é a forma homozigota para a HbS que representa a anemia falciforme (AF) é a mais grave manifestação clínica. Conhecida com distúrbio hereditário da hemoglobina humana, seu portador detém o genes HbS e seu cônjuge com hemoglobina normal (HbA) por sua vez, dará origem a descendentes chamados de "traço falciforme" (HbAS) não manifestará nenhum dos sintomas clínicos cabendo apenas o encaminhamento para orientação genética/educacional (Valêncio & Domingos, 2016;Pereira, et al, 2018). O Programa Nacional de Triagem Neonatal (PNTN) foi estabelecido no Brasil em 2001, com objetivo de ampliar o rastreio de doenças com: fenilcetonúria, hipotireoidismo e doenças congênita como as hemoglobinopatias e fibrose cística em recém-nascidos (RN).…”
Section: Introductionunclassified